Peran Dan Strategi Pondok Pesantren Dalam Meningkatkan Perekonomian Masyarakat di Lingkungan Sekitar - Siti Nur Azizah; Lutfi Hery Rahmawan; Ana Santika (Sharing: Journal of Islamic Economics Management and Business, 2024)
This exploration expects to decide the essential job of Islamic live-in schools in working on the economy of the local area in the general climate. The methodology utilized in this exploration is a subjective examination approach. The information assortment strategies utilized in this examination are: Interview, Perception and Documentation. The consequences of the examination show that in the job of the Hidayatul Mubtadiin Islamic Life experience School, Sidoharjo Town, Jati Agung Locale, South Lampung Regime, they decide to go about as a facilitator among venders and purchasers, and that implies that the Islamic live-in school just permits it. local area to sell different necessary items by all understudies and assist with giving chances to work on the economy of the local area in the climate around the house. By persuading the local area to deliver an item that gives selling esteem and the Hidayatul Mubtadiin Islamic Live-in School gives the open door to the local area to sell the items it produces. For this situation, the Hidayatul Mubtadiin Islamic Live-in School isn't a business entertainer yet rather a consolation and inspiration in arousing the local area to work on its economy. In the mean time, as a supporting variable, there are media that go about as a connection between Islamic life experience schools and the local area, so all Islamic live-in school exercises, including financial exercises, can be passed on to the local area